The effect of job empowerment on job embeddedness An analytical exploratory study in the Baghdad Municipality (مجلة المنصور, 2025)
The research aims to identify the effect of altruistic behavior in strengthening employees’ ties with the organization in the Baghdad Municipality, as the problem is embodied in the following main question: What is the effect of altruistic behavior in strengthening employees’ ties with the organization in the organization under investigation? The importance of research is highlighted in enhancing the feeling of ties with the organization among employees. Employees in the Baghdad Municipality through interest in practicing altruistic behavior. The research adopted the descriptive analytical approach, by surveying the opinions of employees in the Baghdad Municipality regarding the level of interest in the two research variables and analyzing these opinions. (350) questionnaires were distributed, distributed electronically via the (Google Form) program. In addition to distributing part of it directly to some employees who do not have the ability to answer it electronically, the collected data was processed and the research hypotheses were tested by applying a number of statistical methods, including (Cronbach’s alpha, arithmetic mean, standard deviation, Spearman correlation coefficient, and simple linear regression), using the statistical analysis program (SPSS Ver-24). The research reached a set of conclusions, the most prominent of which is the existence of a correlation as well as the effect of altruistic behavior in strengthening employees’ ties with the organization. The research concluded with recommendations, including the need for the senior management of the Municipality of Baghdad to discuss and encourage employees. To adopt the practice of altruistic behavior, which will contribute significantly to strengthening employee ties with the organization.